Kajian Etnofarmasi Kelompok Masyarakat Banjar Subamia Kelong, Tabanan Bali - Perayanthi, Reni; Anita Dewi, Ni Luh Kade Arman; Suradnyana, I Gede Made; Kusuma Yuda, Putu Era Sandhi; Cahyaningsih, Erna; Vernandes Sasadara, Maria Malida; Sugiyanto, Milyadi (Usadha, 2024)
Bali is rich in culture and traditions passed down from generation to generation, especially in the ethnopharmacy aspect as a traditional medecine. This research aims to study ethnopharmacy aspects of the application of herbal plants as traditional medicine including plant parts, processing methods, indications, and usage of herbal plants in Banjar Subamia Kelong, Tabanan, Bali. This research was carried out using survey methods, direct observation in the field, and interviews. This research identified 20 types of plants that are generally used by the community in the Banjar Subamia Kelong. The plant parts generally used are leaves (60%), stems (15%), rhizomes (15%) and fruit (10%). Most of the plants are processed by boiling (60%). These medicinal plants are mostly used orally (65%), and the general indication is to treat joint problems, such as muscle pain and gout (25%).